Dysregulation of stromal derived factor 1/CXCR4 axis in the megakaryocytic lineage in essential thrombocythemia - Salim, Juan Pablo (2009)
This study investigated the involvement of chemokines including stromal derived factor 1 (SDF-1), interleukin 8 (IL-8), growth-related oncogene alpha (GRO-a) and their receptors, CXCR4, CXCR2 and CXCR1 in essential thrombocythemia (ET), a chronic myeloproliferative disease characterized by megakaryocytic hyperplasia and high platelet count. Fifty-three ET patients were studied. Plasma levels of SDF-1, IL-8 and GRO-a, evaluated by enzymelinked immunosorbent assay, and flow cytometric analysis of CXCR1 and CXCR2 on the platelet membrane, were found to be normal in ET patients. CXCR4 expression on platelet surface aswell as platelet CXCR4mRNAdetected by real-time reverse transcription polymerase chain reaction, were decreased. Platelet CXCR4 internalization rate was normal while SDF-1-induced platelet aggregation was delayed, decreased or absent. Immunohistochemical staining revealed that megakaryocytes were also affected. CXCR4 decrease was not observed either in peripheral white blood cells or in circulating CD34+ precursors. These results show that CXCR4 is decreased in the megakaryocytic lineage in ET, mainly due to a reduced CXCR4 production, and an abnormal platelet response to SDF-1. This report is the first to describe platelet and megakaryocytic CXCR4 deficiency in a human disease and the presence of this abnormality in a megakaryocytic-related illness highlights the important role of SDF-1/CXCR4 axis in platelet development.